IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISME MELALUI MODEL PEMBELAJARAN PJBL UNTUK MENINGKATKAN MINAT DAN KEAKTIFAN BELAJAR SISWA KELAS V SDN 2 CINTANAGARA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Basic education is a crucial level of education in shaping students’ character, knowledge, attitudes, and skills. However, many teachers still use conventional teaching methods that are teacher-centered, thus failing to actively engage students. This condition leads to low student interest and participation in learning. This study aims to explore the effectiveness of applying constructivist learning theory through the Project-Based Learning (PjBL) model in increasing students’ interest and active participation in learning at the elementary school level, particularly in rural areas. This research uses a descriptive qualitative approach conducted at SDN 2 Cintanagara, Cigedug District, Garut Regency. The Research subject consisted of 24 fifth-grade students (18 girls and 6 boys). Data collection techniques included questionnaires, observation, interviews, and documentation. Data analysis followed the Miles and Huberman model: data reduction, data display, verification, and conclusion drawing. The results showed that the application of constructivist theory through the PJBL model was effective in increasing students’ interest and active participation in learning. Thus, this approach can be used as an alternative to improve the quality of learning in elementary schools.